Hydroxy-fipronil is a new urinary biomarker of exposure to fipronil. (June 2017) - Vasylieva, Natalia; Barnych, Bogdan; Wan, Debin; El-Sheikh, El-Sayed A.; Nguyen, Hai M.; Wulff, Heike; McMahen, Rebecca; Strynar, Mark; Gee, Shirley J.; Hammock, Bruce D.
Abstract: Occupational medical surveillance is highly desirable in manufacturing facilities where exposure to chemicals is significant. The insecticide fipronil is generally considered safe for humans but with increasing use, exposure to fipronil is of concern. Identification of urinary metabolites of fipronil may allow development of affordable, cheap and rapid procedures for human exposure evaluation. In this study we developed a fast and easy approach for synthesis of hydroxy-fipronil, a potential urinary metabolite of fipronil. This standard was used to develop a sensitive analytical LC-MS/MS method with a limit of quantification (LOQ) of 0.4 ng/mL. Fipronil sulfone, a known metabolite, and hydroxy-fipronil were quantified in urine samples from rats treated with a fipronil containing diet. Fipronil sulfone concentration centered around 20 ng/mL, while the concentration of hydroxy-fipronil was dose-dependent ranging in 10–10, 000 ng/mL and thus being a more sensitive marker of fipronil exposure. A fipronil immunoassay with cross-reactivity to hydroxy-fipronil showed a good correlation in signal intensity with LC-MS data. It was also used to demonstrate the applicability of the method for sample screening in the evaluation of exposure levels. Highlights: Fast and easy approach was developed for the first time synthesis of hydroxy-fipronil, a urinary metabolite of fipronil. Hydroxy-fipronil standard was used to develop a sensitive analytical LC-MS/MS method with a LOQ of 0.4 ng/mL. Hydroxy-fipronil is a more sensitive dose-dependent biomarker of exposure to fipronil compared to fipronil-sulfone. Immunoassay was used for sample screening in the evaluation of exposure levels. Hydroxyl-fipronil was tested in the insect assay and on mammalian GABAA receptors to characterize its biological activity.